PSYCHOLOGICAL DETERMINANTS OF SELF-ASSESSMENT OF YOUNGER SCHOOL STUDENTS (Psychology Travelogs, 2022)
With all the variety of forms of education and pedagogical institutions emerging in modern Ukraine, the main tasks of teaching and raising children and control over these processes remain as before. In the context of the ideas of the person-oriented sphere of education, the problem of assessment in the educational process acquires new forms and content. The significant spread of the phenomenon of evaluation in the educational process of the school is the reason why the teacher's evaluation of the results of the students' educational activities and self-evaluation has been separated into an independent direction in recent years.According to the theory of educational activity, evaluation activity generates the need of a student or teacher to obtain information about whether the quality of knowledge and skills of students in the subject meets the requirements of the program. The purpose of assessment activities is to control the success of students and to form their adequate self-esteem. The subject of the evaluation activity, which coincides with the subject of educational and cognitive activity, is the student's system of knowledge and skills. The result of the act of evaluation by the teacher of the results of the student's educational activity is an evaluation, which, depending on the level and method of reflection of relations, can be expressed by the sign and intensity of emotional experience, an evaluative judgment, a mark.
Keywords: self-esteem; psychological determinants; knowledge; student's ability